Urban Environmental Management Performance Assessment by Fuzzy Analytical Hierarchy Processing (FAHP) - Omidvari, Manouchehr; Ghandehari, Maryan (Journal of Environmental Accounting and Management, 2026)
In recent decades, the world’s population growth and concentration in mega cities have caused several environmental, social and economic problems. Environment management audit has always been considered as a major challenge in urban management. Providing an appropriate model for the raters makes their personal judgments routinely minimized and obtains a more realistic assessment of the present situation. Using Fuzzy Analytical Hierarchy Processing and collating it with audit programs can help them to achieve this goal. In the present research study, using stand- ards, the environmental indices have been determined in urban manage- ment and then using Fuzzy Analytical Hierarchy Processing method, the weight and importance level of the indices have been set and the evalua- tion pattern was presented. The present study was conducted with the aim of presenting a model for auditing the environment and one of Tehran’s municipality regions was selected to do a case study. The results showed that the most important problems in the field of environmental manage- ment in a megacity like Tehran are in areas such as transport and traffic management, waste-water installation and solid waste management which have been unsatisfactory in some areas under study. Applying the pro- posed model has provided urban management with the possibility to iden- tify weaknesses of its collection and remove discrepancies by investing in the issue and causing a continuous improvement of the environment in their management zone.